Demography and Feeding Practices of ICU Patient of Government and Private Hospitals of Jorhat District, Assam - Bordoloi PL; Barooah MS; M. Gogoi (Intelektual Pustaka Media Utama, 2017)
The aim of the present study was to analyze the characteristics and feeding practices of patient admitted to medicine ICUs. All relevant clinical and dietary information were collected for patients admitted to ICUs of selected Government and private hospitals of Jorhat district, Assam. This information was abstracted with the help of pre-structured schedule from the Medical Record Department and Intensive Care Unit team and analysed. A total of 1034 patients were admitted during the study period. Majority of the patients (49.61%) were from the age group of 60years and above. Majority incidence of diseases is a reason of admission in ICUs of both the hospitals was non-communicable diseases and patients were admitted via emergency OPD. Highest length of stay of 10-15 days was observed among the majority of patient from government hospital while it was shorter (6-10 days) for private hospital. The daily feeding pattern of each of the patients was recorded. Patients dependent on homemade blenderized foods for nutritional support were more in Government hospital while compare to the patient using both the commercial formulae as well as homemade food till the last day of stay in private hospitals. Increased cost of hospitalization and better outcome of patient in terms of short stay at hospitals and better nutritional status of the patient admitted to private hospitals were not feasible for low income groups patients admitted in Government hospital. The results of the present study will help the need of formulation and development of patient specific homemade foods with its ingredients used and nutritional requirement in it are taken account for both oral and enteral feedings in the hospitals with higher standard values with all demonstration on the development of protocols for clean techniques in the preparation, safe handling and storage of handmade enteral feeds.